The practice of reason : Leibniz and his controversies - Dascal, Marcelo (Controversies, 2010)
Gottfried Wilhelm Leibniz (1646-1716) dedicated much of his life to some of the most central debates of his time. For him, our chance of progress towards the happiness of mankind lies in the capacity to recognize the value of the different perspectives through which humans approach the world. Controversies supply the opportunity to exercise this capacity by approaching the opponent not as an adversary but as someone from whose point of view we can enrich our own viewpoint and improve our knowledge. This approach inspired the creation of this series. The book - the first in the series devoted t.